2022
DOI: 10.1111/hequ.12374
|View full text |Cite
|
Sign up to set email alerts
|

Students' transition into higher education: The role of self‐efficacy, regulation strategies, and academic achievements

Abstract: Transition into higher education (HE) has received increased interest in recent years, since it represents a challenging period for students. The aim of this study was to further understand the associations between self‐efficacy, academic achievements, and regulation in first‐year university students during their transition into HE. The convenience sample consisted of 374 first‐year university students (230 females, 61.5%), aged from 18 to 33 (M = 19.86, SD = 1.51) and recruited from an Italian university. Sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Additionally, Pintrich (2004) highlighted the importance of self-regulation in goal-setting, learning control, motivation, and behavior. This is consistent with Lin et al's (2023) study, which found that students with higher self-efficacy and self-regulation strategies had better academic performance.…”
Section: These Are the Suggestions From The Studysupporting
confidence: 92%
“…Additionally, Pintrich (2004) highlighted the importance of self-regulation in goal-setting, learning control, motivation, and behavior. This is consistent with Lin et al's (2023) study, which found that students with higher self-efficacy and self-regulation strategies had better academic performance.…”
Section: These Are the Suggestions From The Studysupporting
confidence: 92%
“…When students are autonomously motivated, they reflect, evaluate, and integrate the learning content in line with their own personal interests and goals, and studies have shown that autonomously motivated students exert more effort into learning activities (Reeve et al, 2002;Joussemet et al, 2004;Howard et al, 2021) and are more resilient when facing challenging assignments (Xu et al, 2018(Xu et al, , 2021Lin et al, 2022). Effort has been shown to correlate with both academic achievements, increased recollection, and perceived competence, hence it constitutes a wide aspect of student functioning (Schmid and Bogner, 2015;Xu et al, 2018).…”
Section: Correlates Of Motivation and Student Functioningmentioning
confidence: 99%
“…In the educational path there are many challenging transition periods such as transition to higher education institutions (HEI) or to work life (Lin et al 2023). For example, university studies do not always match with expectations or studies proceed as planned (Jansen and Suhre 2010;Valto and Nuora 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This increases dropout rates that is a major issue for HEIs (Hailikari and Nevgi 2010). Therefore, it is important to ensure an effective transition both for promoting the well-being of young people and remain productive in the educational sector to match the massive constantly growing need for education (Lin et al 2023;Ikävalko, Pernaa, and Aksela 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation